Verticalization of Patients with Severe Acquired Brain Injury: A Randomized Pilot Study - Sadriddin Sayfullaevich Pulatov (Genius Journals, 2022)
A stroke is an acute disorder of cerebral circulation in which an area of the brain dies. Depending on which specific part of the brain is affected, a stroke patient loses certain brain functions and various organs stop functioning. There are two key types of stroke - ischaemic and haemorrhagic. In an ischaemic stroke, the patient suffers a thrombus in one of the cerebral arteries which "clogs". This leads to an end to blood flow through the artery and gradual death of the brain tissue "downstream". Haemorrhagic stroke is a cerebral haemorrhage due to disruption of the integrity of the vascular wall. This type of stroke is less common but the consequences are usually catastrophic. Verticalisation improves the level of arousal and consciousness in patients with severe acquired brain injury (ABI) and is safe in the intensive care unit. We evaluated the effectiveness of a very early step verticalisation protocol on their functional and neurological outcome
Keywords: verticalization; stroke